Estrategias de Desarrollo del Talento Humano en los Estudios Jurídicos, en el cantón La Maná, provincia de Cotopaxi. - Días Pilatasig, Mayra Janneth (2023)
The research work was aimed at improving the management of human talent in the Legal Studies of the canton of La Maná, in the province of Cotopaxi, which arose in the face of the existing deficiencies in the processes of development of human talent. In the preliminary diagnosis, staff turnover was evident, which is attributed to weaknesses in the training of skills, incentives and work motivation, leading to the disengagement of collaborators. The objective was established to design strategies for the development of employee talents that contribute to better performance of the position and increase their productivity in legal establishments. The methodology was framed in a qualitative approach, supported by the descriptive method. The population under study included 30 partners of the law firms from whom information was collected through the survey technique using a questionnaire. The results revealed shortcomings in the development of human talent: 70% of employees indicated few possibilities for professional growth, 70% indicated a low level of job stability, 63% stated that they felt unmotivated and 83% showed a willingness to participate in training programs. Consequently, strategies were established that will allow the assessment of intellectual capital, based on strategies for incorporation, placement, rewards, retention and supervision of human talent.